Field Research on Translation and Interpreting (John Benjamins Publishing Company, 2025)
This volume constitutes a significant step in establishing field research as a central methodological approach in translation and interpreting studies. Following an integrative approach, it addresses both translation and interpreting across professional, paraprofessional, and non-professional settings. The chapters in this volume focus on lived experiences in diverse, real-world contexts—including refugee centres, UN missions, NGOs, virtual environments, and the workplaces of specialised translators. They offer rich insights into the situated and dynamic nature of translation and interpreting practices and discuss common aspects and challenges such as the researchers’ reflexivity, ethical considerations, and the role of materiality in fieldwork. By shedding light on underexplored areas and offering critical reflections on field research methodology, the volume contributes to expanding the boundaries of translation and interpreting studies and deepening our understanding of translation and interpreting in their social and material contexts.